Problems of organising the solid municipal waste collection in residential buildings - A. N. Kirillova; N. N. Musinova (Вестник университета, 2022)
The functioning of the regional operators’ territorial infrastructure of solid municipal waste management revealed a number of problems. The article considers the initial phase of the solid municipal waste management life cycle – the organisation of separate waste collection, which requires joint construction, technological, financial and social solutions, with close cooperation between the state, business and the population. The need to introduce new technologies for the organic waste separate collection, new design solutions in residential buildings under construction for the solid municipal waste separate collection has been noted. In order to monitor waste management processes, coordinate and make decisions to ensure their sustainable functioning, it has been proposed to form an automated information system at the federal level allowing communication to close all regional operators into a unified sectoral information system.